2013
DOI: 10.1080/10402004.2011.651772
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Dynamics of Synthetic-Based Lubricant System by Spectroscopic Techniques—Part 1

Abstract: This article describes the structure-property relationships of synthetic pentaerythritol polyol esters (PEE) and polyalphaolefins (PAO) as established by the diffusion and mobility measurement and tilt angle results obtained by nuclear magnetic resonance (NMR) and infrared (IR) spectroscopic techniques, respectively. The diffusion coefficients (D) were found to be dependent on the molecular structure, alkyl chain length, shape and size, hydrodynamic volume, and alignment of the molecules in a lubricant system … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Thus, it is imperative to screen suitable lubricant base oils and additives in order to guarantee the safe operation of the engines at high temperatures. Compared with mineral oil and bio-oil, synthetic esters usually exhibit excellent viscosity temperature properties, good low-temperature fluidity, and high antioxidation ability. , In particular, their superior thermal oxidation stability compared to that of mineral oil makes them promising candidates as high-performance lubricants with desired performance at elevated temperatures. However, synthetic esters are still susceptible to chemical reactions with oxygen and water as well as metal under elevated temperatures, thereby quickly losing lubricity and frequently needing replacement. , In this respect, it is imperative to introduce antioxidants to prevent synthetic ester oils from oxidative degradation, thereby prolonging their service life in tribological applications …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, it is imperative to screen suitable lubricant base oils and additives in order to guarantee the safe operation of the engines at high temperatures. Compared with mineral oil and bio-oil, synthetic esters usually exhibit excellent viscosity temperature properties, good low-temperature fluidity, and high antioxidation ability. , In particular, their superior thermal oxidation stability compared to that of mineral oil makes them promising candidates as high-performance lubricants with desired performance at elevated temperatures. However, synthetic esters are still susceptible to chemical reactions with oxygen and water as well as metal under elevated temperatures, thereby quickly losing lubricity and frequently needing replacement. , In this respect, it is imperative to introduce antioxidants to prevent synthetic ester oils from oxidative degradation, thereby prolonging their service life in tribological applications …”
Section: Introductionmentioning
confidence: 99%
“…Compared with mineral oil and bio-oil, synthetic esters usually exhibit excellent viscosity temperature properties, good low-temperature fluidity, and high antioxidation ability. 4,5 In particular, their superior thermal oxidation stability compared to that of mineral oil makes them promising candidates as high-performance lubricants with desired performance at elevated temperatures. However, synthetic esters are still susceptible to chemical reactions with oxygen and water as well as metal under elevated temperatures, thereby quickly losing lubricity and frequently needing replacement.…”
Section: Introductionmentioning
confidence: 99%
“…Bantchev et al studied the film-forming properties of several blends including bio-based esters [30,31]. Sarpal et al reported the structure-property relationships of pentaerythritol polyol esters and PAOs based on the diffusion and mobility measurement and tilt angle results [32]. However, there were few reports on how the molecular structures and types of synthetic ester base stocks affect the elastohydrodynamic lubrication properties and friction behaviors.…”
Section: Introductionmentioning
confidence: 99%